Nahdlatul Ulama: Telaah Histori Perkembangan dan Gerakan Dakwahnya di Indonesia - Siti Umi Taslima (STAI Bumi Silampari, 2020)
Nahdlatul Ulama (NU) is a traditional ulama organization that has a large number of followers, the largest non-governmental organizations still survive and have roots in the lower classes. This paper aims to describe the history of the development and the da'wah movement of this large organization. The reading presentation in this paper is the author's adoption of various literatures, which the author extracts so that it becomes an interesting article for all readers. From this search and study of literature sources, it is hoped that a complete understanding of NU will emerge, which in recent times has often been described in various dynamics.